"Bad" Politics and "Good" Culture: New Approaches to the History of the Weimar Republic. Issue 3 (18th January 2017) - Hung, Jochen
Abstract : More than thirty years ago, Eberhard Kolb commented that the vast wealth of research on the history of the Weimar Republic made it "difficult even for a specialist to give a full account of the relevant literature." Since then, the flood of studies on Weimar Germany has not waned, and by now it is hard even to keep track of all the review articles meant to cut a swath through this abundance. Yet the prevailing historical image of the era has remained surprisingly stable: most historians have accepted the master narrative of the Weimar Republic as the sharp juxtaposition of "bad" politics and "good" culture, epitomized in the often-used image of "a dance on the edge of a volcano." Kolb, for example, described "the sharp contrast between the gloomy political and economic conditions … and the unique wealth of artistic and intellectual achievement" as "typical of the Weimar era." Detlev Peukert, arguably the most innovative scholar of Weimar history, criticized this historical image but, at the same time, declared this dichotomy "an integral feature of the era." The latest example can be found in the work of Eric D. Weitz, who summarizes the fate of Weimar Germany as "the striving for something new and wonderful encountering absolute evil, " juxtaposing the "sparkling brilliance" of modernist masters like Bertolt Brecht, Thomas Mann, and Bruno Taut with "the plain hatred of democracy" of Weimar's right-wing extremists. This contrasting of politics and culture is a narrative device that only makes sense, however, from our contemporary vantage point of Western liberal democracy and from our understanding of progressive art. This retrospective interpretation is not in itself the problem—after all, historians can never really escape their own historical contexts. It becomes problematic, however, when it is treated not as an interpretation but as historical fact. Weimar Germans certainly would not have shared this narrative wholeheartedly: many would not have subscribed to the depiction of their time as a never-ending parade of political breakdowns and economic disasters. Even more would have rejected the view of the Berlin-based avant-garde as a sign of progressive achievement—if they had ever had the chance to see its representative works in the first place. The sharp distinction between "bad" Weimar politics and "good" Weimar culture not only fails to do justice to the way many of these Germans perceived their time but also keeps us from understanding how closely intertwined these two spheres were in the Weimar Republic. Thus, rather than giving an overview of the latest additions to Weimar historiography, this review essay looks at how recent publications have questioned—or conformed to—this dominant narrative.